SEROPREVALENCE AND RISK FACTORS FOR HUMAN TOXOPLASMOSIS IN NORTHEASTERN BRAZIL - de Almeida Aloise, Debora; Coura-Vital, Wendel; Carneiro, Mariangela; Venâncio Rodrigues, Marlus; Acásia da Silva Toscano, Gislani; Bernardino da Silva, Ramiza; Ferreira de Andrade Neto, Valter; Wagner Almeida Vitor, Ricardo (Revista de Patologia Tropical / Journal of Tropical Pathology, 2018)
Toxoplasmosis is one of the most prevalent parasitic infections in humans, causing severe clinical complications in immunocompromised patients or in foetuses. Estimates on the toxoplasmosis seroprevalence in human populations vary widely, even within the same region. This study aimed to estimate the prevalence of Toxoplasma gondii infection in the municipality of Santa Cruz, State of Rio Grande do Norte, Brazil, and identify the risk factors for toxoplasmosis. T. gondii IgG antibodies were measured in 66.2% of the studied population. The factors associated with infection were as follows: age above 45 years (OR = 7.4; 95% CI = 3.7-14.8); illiteracy (OR = 2.8; 95% CI = 1.6-5.0); the presence of more than three cats in the home (OR 2.0; 95% CI = 1.2-3.5); no water tank (OR = 2.0; 95% CI = 1.4-3.1); and consumption of raw or unpasteurized milk (OR = 2.0; 95% CI = 1.3-3.0). The risk factors identified were predominantly related to the ingestion of oocysts. This study may contribute to public health knowledge of toxoplasmosis and the definition of control programs, particularly for pregnant women from regions similar to the area studied.